Is there a real difference between modular stems and monoblock implants in THA? A revision and comparison of tribological, clinical and radiological outcomes - Manfreda, Francesco; Bufi, Egzon; Talesa, Giuseppe Rocco; Florio, Enrico Francesco; Caraffa, Auro (Lo Scalpello - Journal, 2022)
Background. Total hip arthroplasty represents one of the most practiced intervention in orthopaedic surgery. In order to increase the durability of implants, several options have been proposed over the years. Probably one of the most important aspects for this purpose is the adequate restoration of the offset, limb length and femoral neck version. The appearance of modularity in implants seems to be the best help for orthopaedists to achieve these goals. However, in view of these advantages, some specific complications of modular prostheses have been reported, including increased release of metal particles from wear, fretting, implant failure and secondary osteolysis. Aim. The aim of this study was to conduct a systematic review of the studies in the literature in order to compare modular implants with monolithic implants from a tribological, clinical and radiographic point of view and to establish specific indications or contraindications. Methods. We set specific and clear inclusion criteria and selected 11 studies from a collection of more than 150 studies found in the principle scientific databases. We analysed the studies by dividing them by categories of outcomes and assessing any differences between them. Findings. No significant differences were found in almost any of the outcomes examined. The only different trend was shown in the blood and urinary concentration of metal ions resulting from corrosion, which was increased in modular prostheses. However, this difference was not reflected in a cross-evaluation with clinical and radiographic outcomes. Conclusions. The literature is poor in valid scientific evidence that compares the two groups of patients. There is no unanimous opinion on any evaluable outcome. Further RCTs and meta-analyses on this much debated topic are needed.